2009
DOI: 10.1016/j.immuni.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Mediated Autoimmune Disease Due to Low-Affinity Crossreactivity to Common Microbial Peptides

Abstract: Environmental factors account for 75% of the risk of developing multiple sclerosis (MS). Numerous infections have been suspected as environmental disease triggers, but none of them has consistently been incriminated, and it is unclear how so many different infections may play a role. We show that a microbial peptide, common to several major classes of bacteria, can induce MS-like disease in humanized mice by crossreacting with a T cell receptor (TCR) that also recognizes a peptide from myelin basic protein, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(108 citation statements)
references
References 44 publications
1
107
0
Order By: Relevance
“…be associated with an autoimmune disease (45,46), it is likely that certain host-specific factors induced by common pathogen-associated molecules might contribute to the triggering autoreactive T cells. Several recent studies have highlighted the importance of the inflammatory cytokines IL-6 and IL-21 and the homeostatic cytokines IL-7 and IL-15 in autoimmune diseases (7, 8, 10-12, 33, 47, 48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…be associated with an autoimmune disease (45,46), it is likely that certain host-specific factors induced by common pathogen-associated molecules might contribute to the triggering autoreactive T cells. Several recent studies have highlighted the importance of the inflammatory cytokines IL-6 and IL-21 and the homeostatic cytokines IL-7 and IL-15 in autoimmune diseases (7, 8, 10-12, 33, 47, 48).…”
Section: Discussionmentioning
confidence: 99%
“…However, it still remains to be answered how autoreactive CD8 T cells in the peripheral circulation, which bear TCRs with low reactivity toward self-Ags because of the thymic selection process (5), gain the ability to respond to autoantigens. In this context, it is noteworthy that diverse peptides with weak reactivity toward the TCR can be cross-reactive because of structural mimicry (46). Similarly, heterologous virus infection has been shown to activate low-avidity autoreactive CD8 T cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…+ T cell-mediated demyelinating disease with pathological similarities to MS and is widely used as an animal model of MS (1,2). EAE is induced in susceptible mice by immunization with whole myelin proteins, MOG peptide, or PLP peptide emulsified in CFA, or by adoptive transfer of autoreactive T cells to normal recipient mice (3)(4)(5)(6).…”
Section: Ultiple Sclerosis (Ms) Is the Most Common Autoimmune Inflamentioning
confidence: 99%
“…One of the facets of polyspecificity in the context of autoimmune diseases is molecular mimicry, defined as sequence similarities between foreign and self-antigens that result in the cross-activation of autoreactive T and B cells by microbial Ags (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Originally, an important degree of sequence homology was considered necessary to explain molecular mimicry, but subsequent extensive dissection with synthetic peptide combinatorial libraries revealed that TCR Ag recognition is quite degenerate, and Ag similarity, resulting in the productive triggering of a given TCR, goes beyond sequence homology (10,38,39).…”
mentioning
confidence: 99%